(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In recent years, there has been an increase in the prevalence of food allergies and atopic dermatitis. Thus, in the early 90s, according to epidemiological studies conducted in different countries, its level among children was 3-4%, and in early childhood - 5-8%. Also, the proportion of children sensitized to potentially dangerous food allergens in the population is increasing, which causes an increase in the prevalence of food anaphylaxis. The prevalence of atopic dermatitis is increasing. In Uzbekistan, according to ISAAC, the prevalence of atopic dermatitis among children is 6.7%-12.3% of cases. At the same time, the treatment of young children suffering from atopic dermatitis and food allergies is accompanied by serious difficulties in choosing the optimal elimination diet and. pharmacotherapy. The relationship between atopic dermatitis and food allergies has been known for a long time. At the same time, there are still significant disagreements in determining the contribution of food allergy to the development of atopic dermatitis in children. According to various authors, the prevalence of food allergy among children suffering from moderate and severe atopic dermatitis ranges from 20 to 80%. In addition, the significance of specific food products in the development of food allergy manifestations has not been sufficiently determined. The role of food allergy in the development of atopic dermatitis is largely associated with the induction of synthesis and release of mediators of allergic inflammation, which, in particular, include eosinophilic cationic protein (ECP). The significance of ECP in the formation of clinical manifestations of atopic dermatitis has previously been studied by a number of authors, but the data obtained on the relationship between the level of ECP and the severity of atopic dermatitis were contradictory. It can be assumed that this circumstance is associated with the heterogeneity of patients with atopic dermatitis. On the other hand, it is possible that food allergy causes activation of esinophilic inflammation, which affects the severity of atopic dermatitis. One of the urgent scientific and practical problems is predicting the course of food allergy. The solution to this problem will allow us to identify groups of children with persistent and transient food allergy; establish possible time frames for the development of food tolerance; and optimize the elimination diet. In addition, identifying children with persistent food allergy will probably allow us to determine indications for the use of methods for inducing tolerance to food products. Currently, a number of criteria are being actively developed (the level of specific immunoglobulins of class E; the type of immunopathological reaction (immediate or delayed)), which, with a certain degree of probability, allow us to determine the prognosis of the course of food allergy. It has been shown that there is a relationship between the level of specific immunoglobulins E and the cessation of clinical manifestations of food allergy. However, to date, it is impossible to accurately indicate the threshold level of specific IgE at which tolerance will develop with a high probability. The view on changes in the level of specific IgE in the serum as a criterion for the development of clinical tolerance still remains ambiguous. Currently, there are isolated studies devoted to the study of indicators of the state of cellular immunity (subpopulation composition of T-cells) as criteria for predicting the development of tolerance in children with food allergies, and the question of the role of regulatory cells in the development of food tolerance has not yet been resolved.